Pengaruh Pijat Bayi Terhadap Kuantitas Tidur Bayi Usia 3-6 Bulan Di Kelurahan Sempaja Selatan Samarinda - Saidah, Siti; Lidia, Besse; Fauziah, Fauziah (Bunda Edu-Midwifery Journal (BEMJ), 2020)
Sleep is a top priority for infants, because this is when neuro-brain repair occurs and approximately 75% of growth hormone is produced. Given the importance of sleep time for a baby's development, his sleep needs must be met so as not to adversely affect his development. One way that can be used to meet these needs is by infant massage. The purpose of this study is to prove that massage can increase the quantity of sleep for infants aged 3-6 months in Sempaja Selatan Village, North Samarinda. The research design used Pre Experiment Design with One Group Pretest-Postest Design. The population in this study were all babies aged 3-6 months consisting of 18 respondents with the sampling technique using Non Probability Sampling selected by purposive sampling. The variable measured in this study was the quantity of baby sleep. This study used the Paired t-test statistical test (α = 0.05). The results showed the quantity of baby sleep after massage was higher (13.77 hours / day) than before massage (12.42 hours / day) with an average increase of 1.29 hours / day. The results of statistical tests showed that there was an effect of infant massage on the quantity of sleep for infants aged 3-6 months with a value (p = 0.000). Thus it can be concluded that there is a significant effect of infant massage on the quantity of baby sleep. The need for the role of health workers to develop promotion and education about baby massage to the community, especially parents, to increase the quantity and quality of baby sleep